PENGARUH MANAJEMEN STRES PADA MASA PANDEMI COVID 19 TERHADAP STRESS MASYARAKAT DI DUSUN GARUNG DESA BANGERAN - MOJOKERTO - Nurul Mawaddah, S.Kep.,Ns.,M.Kep; Agung Nurdiansah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Policies about studying, working, and worshiping at home need to be intensified to reduce the spread of Covid-19. The high number of the spread of the Covid 19 virus causes a lot of stress in the community.This study aimed to determine the effect of stress management during the Covid 19 pandemic on community stress in Garung, Bangeran Mojokerto. The research design was a pre-experimenta, wich used one group pretest-posttest design. The number of samples was 36 respondents that selected by using simple random sampling technique. The study was conducted in February-March 2021. The results showed that the majority of respondents had a severe stress levelas many as 19 (52.8%) and after being given stress management, it was found that most of the respondents have a moderate stress level(63, 9%). Wilcoxon statistical test showed p value = 0.000. Which means that there is an effect of stress management during the Covid 19 pandemic on community stress. So people must do management to face covid 19 pandemic effect by doing religious lecturing, reading Q.S yasin, istighosah and praying